GAMBARAN PENGELOLAAN LIMBAH MEDIS PADAT DI RUMAH SAKIT Hi MUHAMMAD YUSUF KALIBALANGAN KOTABUMI TAHUN 2019 - Arisma, Nova (Ruwa Jurai: Jurnal Kesehatan Lingkungan, 2021)
Hi Muhammad Yusuf Hospital produces about 2.4 kg of solid medical waste per day. The initial survey results found that solid medical waste has not been appropriately managed, even though this waste can be a source of health problems for the community. This study aimed to describe the management of solid medical waste at the Hi Muhammad Yusuf Hospital, Kalibalangan, Kotabumi. This research describes the management of solid medical waste from source, type, weight, sorting, container, collection, and temporary storage. Data were collected through observation and interviews with medical waste management officers. Furthermore, the data is compared with Minister of Health Regulation No. 7 of 2019. Solid medical waste management is declared to meet the requirements if it is following the regulation. The process of sorting, storing, and transporting hospital waste does not meet the requirements. There is still solid medical waste mixed with non-medical waste. Hospitals need to provide medical bags in brown for pharmaceutical waste, red for radioactive waste, and purple for cytotoxic waste. Training for waste management officers is needed to improve understanding of solid medical waste management and the availability of SOPs as a guide for waste management officers.